2017
DOI: 10.3390/ijms18071405
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Promotes Hepatic Synthesis of Long-Chain Polyunsaturated Fatty Acids by Regulating ELOVL5 at Post-Transcriptional Level in Laying Hens

Abstract: Abstract:The very long chain fatty acid elongase (ELOVL) plays an important role in the synthesis of long-chain polyunsaturated fatty acids (LCPUFA). Previous studies suggest that chicken could be an alternate source of eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). In this study, we detected that ELOVL5, which plays a key role in the biosynthesis of omega-3 (n-3) and omega-6 (n-6) polyunsaturated fatty acids (PUFA), was highly expressed in the liver of laying hens and increased rapidly after sexu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 36 publications
0
24
0
Order By: Relevance
“…Several studies have reported co-expression between miRNA and the host gene. For example, miR-218-5p is located in intron 14 of the slit guidance ligand 2 (SLIT2) gene and co-expressed in the synthesis of long-chain polyunsaturated fatty acids ( Zhang M. et al, 2017 ). Also, miR-932 and the host gene Drosophila neuroligin2 (dnlg2) were co-expressed in Drosophila head ( Qian et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported co-expression between miRNA and the host gene. For example, miR-218-5p is located in intron 14 of the slit guidance ligand 2 (SLIT2) gene and co-expressed in the synthesis of long-chain polyunsaturated fatty acids ( Zhang M. et al, 2017 ). Also, miR-932 and the host gene Drosophila neuroligin2 (dnlg2) were co-expressed in Drosophila head ( Qian et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…SREBP-1 is the main transcription factor involved in such a feedback regulatory process [ 19 , 20 ], while LXR is described as another regulator of elovl5 in fish [ 21 , 22 , 23 ]. Recently, Laying Hens and his group demonstrated that estrogen could promote hepatic LC-PUFA biosynthesis by regulating Elovl5 at post-transcriptional level, suggesting that there were different regulatory mechanisms between mammals and teleost [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…miR-29 and miR-486 are reported to regulate cholesterol metabolism by targeting hydroxy-3-methyl-glutaryl-CoA reductase and histone acetyltransferase-1, respectively (17,28). Furthermore, miR-30b-5p and miR-30c-5p belong to the same family of miRNAs regulating fatty acid synthesis genes, targeting elongation of very long chain fatty acids protein 5 (ELOVL5) and fatty acid synthase (FAS), respectively (18,19). miR-34a has been reported to participate in proinflammatory NAFLD (24), while miR-130a-3p directly targets transforming growth factor-β receptors 1 and 2, which may contribute to hepatic fibrosis (21).…”
Section: Discussionmentioning
confidence: 99%